2015
DOI: 10.1016/j.pbb.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Adult emotionality and neural plasticity as a function of adolescent nutrient supplementation in male rats

Abstract: The present study explored the effects of supplementing male rats with either choline, omega-3 fatty acids, or phytoestrogens, from weaning into early adulthood, on emotionality and hippocampal plasticity. Because of the neuroprotective properties of these nutrients, we hypothesized that they would positively affect both behavior and hippocampal function when compared to non-supplemented control rats. To test this hypothesis, male Sprague Dawley rats were assigned to one of four nutrient conditions after weani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 78 publications
0
11
3
1
Order By: Relevance
“…Past research indicates that dietary supplementation with choline increases cell proliferation and hippocampal neurogenesis (Glenn et al, 2007; 2008; McCall et al, 2015) and accordingly the prenatal choline supplementation of the current study was expected to combat reductions in these markers caused by MK-801 in adult rats. In accordance with this hypothesis, the current investigation revealed that choline-supplemented rats given MK-801 had significantly more newly-divided cells in the dentate gyrus compared to standard-fed rats given MK-801.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Past research indicates that dietary supplementation with choline increases cell proliferation and hippocampal neurogenesis (Glenn et al, 2007; 2008; McCall et al, 2015) and accordingly the prenatal choline supplementation of the current study was expected to combat reductions in these markers caused by MK-801 in adult rats. In accordance with this hypothesis, the current investigation revealed that choline-supplemented rats given MK-801 had significantly more newly-divided cells in the dentate gyrus compared to standard-fed rats given MK-801.…”
Section: Discussionmentioning
confidence: 91%
“…Though dietary choline supplementation is protective throughout the lifespan (Zeisel, 2006), a greater protective capacity is exhibited when the supplementation occurs in early development as opposed to in adolescence or in adulthood (Meck et al, 2008; Wong-Goodrich et al, 2008a; Glenn et al, 2012). Early life choline supplementation in rats, either prenatally, neonatally, or post-weaning, exerts neuroprotection in a wide array of disease models, including epilepsy (Wong-Goodrich et al, 2008b; 2011), Down syndrome (Strupp et al, 2016), Rett syndrome (Nag and Berger-Sweeney et al, 2007; Nag et al, 2009), fetal alcohol syndrome (Thomas et al, 2003; 2007; Schneider and Thomas, 2016), depression (Glenn et al, 2012; McCall et al, 2015: Schulz et al, 2014), and schizophrenia (Corriveau and Glenn, 2012; Stevens et al, 2008; 2014). In addition to these disease models, early life choline supplementation also attenuates the effects of exposure to the neurotoxin, MK-801 (Guo-Ross et al, 2002; 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-fixed brains were sectioned through the rostral-caudal extent of the hippocampal formation on a vibratome with every 4 th 40-µm section retained for doublecortin (DCX) immunohistochemistry, which was conducted as previously described (Glenn et al, 2007; McCall et al, 2015). Briefly, free floating sections were rinsed in Tris-buffered saline (TBS; pH 7.3) and treated with 0.6% hydrogen peroxide for 30 minutes followed by incubation in 0.1% Triton X-100 (TTX; Sigma-Aldrich Corp., St. Louis, MO) and 3% normal horse serum (NHS; Vector Laboratories, Burlingame, CA) at room temperature to reduce non-specific staining.…”
Section: Methodsmentioning
confidence: 99%
“…Using the same sections, estimates of the volume of dentate gyrus sampled in each rat was obtained based on the boundaries of the contour tracings and final estimates of numbers of DCX-labeled neurons are shown as numbers per volume of dentate gyrus. This method minimizes the contribution of differences in the contour region traced or region size among rats or groups, particularly occurring as a result of brain size differences between females and males (McCall et al, 2015). …”
Section: Methodsmentioning
confidence: 99%